Two new species of the subfamily Mydaeinae (Diptera: Muscidae) from China - Wang, Yameng; Li, Wenliang; Li, Xin; Yang, Ding (Zootaxa, 2023)
Keys of the genera Hebecnema Schnabl, 1887 and Mydaea Robineau-Desvoidy, 1830 from China based on males are provided, including two new species Hebecnema kongi Wang, Li & Yang, sp. nov. and Mydaea apicinigra Wang, Li & Yang, sp. nov., respectively. Photographs of habitus and male genitalia as well as illustrations of the male genitalia of the new species are given.